Analysis of airfield composite pavement rutting using full-scale accelerated pavement testing and finite element method. (11th October 2021) - Ling, Jianming; Ren, Liang; Tian, Yu; Gao, Jianhua; Man, Li
Highlights: The finite element model (FEM) was established and verified with a full-scale APT field. Rutting characteristics of airfield composite pavement (ACP) were investigated with APT and FEM. The development law of ACP rutting deformations was explored by the validated FEM. Abstract: Rutting is a typical distress of hot-mix asphalt (HMA) overlays on airfield composite pavements (ACPs). An approach is needed that can provide comprehensive and reliable evaluation of ACP rutting characteristics. In this study, we developed a finite element model (FEM) that was based on parameters derived from laboratory and field tests performed in China. The FEM exhibited satisfactory accuracy after validated by the full-scale accelerated pavement testing (APT) [1]. The test results indicate that a typical dual-wheel rutting profile of ACP exhibits a non-uniform W-shaped deformation with double peaks in a two-stage development process. Variations in temperature, driving states, and interface bonding conditions influence ACP rutting characteristics significantly in terms of increasing deformations (uplift and sag) and changing profiles (with double peaks or single peak). The aircraft load level and overlay thickness only affect the degree and scope of rutting deformations. Rut depth has a power-function relationship with temperature and load cycles, but has a linear relationship with tire pressure and overlay thickness. The uplift coefficients are stable between approximately 0.26 and 0.29 when the influential factors are varied.